ChemInform Abstract: Regiospecific Intermolecular Aminohydroxylation of Olefins by Photoredox Catalysis. Issue 1 (17th December 2015) - Miyazawa, Kazuki; Koike, Takashi; Akita, Munetaka
Abstract: The present photocatalytic system enables regiospecific intermolecular three‐component aminohydroxylation of olefins bearing a wide variety of functionalities.